2021
DOI: 10.1016/j.jtumed.2021.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of COVID-19 and associated factors in a medical institution in Pakistan

Abstract: Objective This study investigates the association of preventive measures with coronavirus disease (COVID-19) seropositivity. Methods This cross-sectional study was conducted at the Combined Military Hospital Kharian Medical College, Pakistan, in September 2020. A total of 442 participants from three different strata (faculty, students, and administration/technical staff) were enrolled using a convenient sampling technique. A rapid antibody testing method was used to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
1
2
1
Order By: Relevance
“…Additionally, the individuals washing their hands regularly were probably shaking hands with other individuals or not maintaining social distance leading to the high seroprevalence. The ndings are inconsistent with other studies, as (15) reported a signi cant association between washing hands, wearing masks, and reduction in seropositivity. Nonetheless, the ndings on the reduction of seroprevalence through social distancing corroborated this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Additionally, the individuals washing their hands regularly were probably shaking hands with other individuals or not maintaining social distance leading to the high seroprevalence. The ndings are inconsistent with other studies, as (15) reported a signi cant association between washing hands, wearing masks, and reduction in seropositivity. Nonetheless, the ndings on the reduction of seroprevalence through social distancing corroborated this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, our study determined that the majority of respondents who developed SARS-CoV-2 antibodies did not develop symptoms, which may be due to abortive infections or asymptomatic infections. This finding was consistent with the results of Naiyar et al, 2021, who determined the seroprevalence of SARS-CoV-2 in a medical institution and stated that most (68.42%) of the technical staff and administrators who had positive IgG were asymptomatic [32]. Nevertheless, the asymptomatic individual can act as the source of the disease (silent transmission), as asymptomatic infections have the same infectivity as symptomatic infections [9].…”
Section: Plos Onesupporting
confidence: 90%
“…After obtaining serum samples, for patients with prior SARA-CoV-2 infection, Ichroma -which is a COVID-19 IgG antibody test against virus nucleocapsid protein (NP) with sensitivity and specificity of 95.8% and 97.0%, respectively -was used as a medical instrument for in vitro diagnosis [16]. A positive result was defined as an IgG level of 1.1 or more [17]. As the coronavirus spike (S) protein serves as the immunogen in all approved vaccines (except Sinopharm, which is based on the inactivated virus) [18], an antibody against S protein was used as a measure for humoral immunity elicited by these vaccines [19,20].…”
Section: Measurements and Instrumentsmentioning
confidence: 99%